Savings transition in Asia: Unity in diversity - Premachandra Athukorala; Wanissa Suanin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper examines the national savings behaviour in the process of economic growth through a comparative analysis of countries in developing Asia from a historical perspective. Developing Asia provides an ideal laboratory for the study with considerable differences in the savings behaviour among countries and over time within individual countries, notwithstanding the 'model saver' image based on the average savings rate. The empirical analysis distinguishes between private and government savings rates, with specific emphasis on the former. The results of the empirical analysis are consistent with the view of 'virtuous circle' between growth and savings, with growth initiating the savings transition. No evidence to suggest that a prior phase of promoting savings through specific policy initiatives is needed to initiate the process of growth and structural transformation. The private savings rate is associated positively with per capita gross domestic product, export orientation, and foreign resource inflows and negatively with the young dependency ratio of the population and domestic credit availability.
Keywords: D15; E21; O47; O53; 330; developing Asia; savings; life cycle model; export-led growth; structural transformation